Absorption Line Profile of the 5S2o-5P1 Transition of Atomic Oxygen and Its Application to Plasma Monitoring. (21st June 2009) - Sasaki, K.; Okumura, Y.; Asaoka, R.
Abstract : The line profile of the 5 S 2 o - 5 P 1 transition of atomic oxygen was measured by diode laser absorption spectroscopy. As a result, it was found that the absorption line profile had a wing component in the wavelength range detuned from the line center and was not fitted with a Gaussian function. The wing component was considered to be originated from dissociative excitation of molecular oxygen. We fitted the absorption line profile with the superposition of two Gaussian functions corresponding to high and low translational temperatures. We propose that the ratio of the high-temperature to low-temperature components is useful for monitoring the relative degree of dissociation of molecular oxygen in oxygen-containing plasmas. The ratio of the high-temperature to low-temperature components was compared with the survival ratio of molecular oxygen, which was evaluated from the lifetime ofO ( 5 S 2 o ) in the afterglow of pulsed discharges.